2017
DOI: 10.17352/2455-2968.000034
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Site Infection: The Rate and Antimicrobial Sensitivity Pattern in Electively Operated Surgical and Gynecological Patients at Kilimanjaro Christian Medical Centre, Northern Tanzania

Abstract: Background: Surgical site infections are dreaded by many as they impose a greater economic costs, morbidity and mortality that in developing countries place a burden on an already burdened healthcare system. In Tanzania previously studies done in different centers reported high rates of Surgical Site Infection. This study aimed to quantify in a low income, tertiary hospital, the rate of Surgical Site infections, microorganisms implicated and their respective sensitivity pattern to local antibiotics, and associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 20 publications
1
3
0
Order By: Relevance
“…Almost all patients in the current study received single antibiotic preoperatively (99%). Similarly other studies have shown that single preoperative of antibiotic prophylaxis could decrease, occasionally dramatically the risk of SSIs [50]. A Study done in our country also showed significant reduction in SSIs when single preoperative prophylactic antibiotic was used.…”
Section: Surgical Antibiotic Prophylaxis Patternsupporting
confidence: 82%
See 1 more Smart Citation
“…Almost all patients in the current study received single antibiotic preoperatively (99%). Similarly other studies have shown that single preoperative of antibiotic prophylaxis could decrease, occasionally dramatically the risk of SSIs [50]. A Study done in our country also showed significant reduction in SSIs when single preoperative prophylactic antibiotic was used.…”
Section: Surgical Antibiotic Prophylaxis Patternsupporting
confidence: 82%
“…Also a study done at KCMC found out that about 30% of patients who got prophylactic antibiotics (ampicillin) developed SSIs as compared to 15.6% who didn't get prophylactic antibiotics. The author attributed these unexpected results to confounders, after accounting for other factors [50].…”
Section: Association Between Surgical Antibiotic Prophylaxis and Surg...mentioning
confidence: 99%
“…However, in Africa, surgically related mortality is twice the global average, and postsurgical infection rates are 2 to 10 times higher than the global average [ 3 ]. In Tanzania, where the maternal mortality ratio is among the highest in the world (556 per 100,000 live births) [ 4 ], studies report surgical site infection rates that are 5–18 times higher than rates in high-income countries [ [5] , [6] , [7] , [8] ]. While long-term strategies to strengthen health systems and increase the health workforce are needed to improve access to high-quality surgical care in lower-income settings, clinical mentorship offers a promising intervention to build the capacity of surgical teams in ways that improve health outcomes in the near term [ [9] , [10] , [11] , [12] ].…”
Section: Introductionmentioning
confidence: 99%
“…7 Studies in Tanzania have reported high surgical site infection (SSI) rates ranging from 21.3% to 48.0% among patients undergoing surgery, including CS. [8][9][10][11][12][13] These rates are 5-18 times higher than rates in high-income countries.…”
Section: Introductionmentioning
confidence: 99%